1997
DOI: 10.1038/bjc.1997.497
|View full text |Cite
|
Sign up to set email alerts
|

Deletion mapping and linkage analysis provide strong indication for the involvement of the human chromosome region 8p12-p22 in breast carcinogenesis

Abstract: Summary We have identified a high frequency of loss of heterozygosity (LOH) on the human chromosome region 8p12-p22 in a panel of microdissected familial (86% LOH) and sporadic (74% LOH) breast tumours. The two most frequently deleted regions were defined around marker D8S1 33 and in a broader centromeric region bounded by markers D8S1 37 and D8S339. We cannot unequivocally characterize the 8p12-p22 loss as an early or a late event in breast carcinogenesis. In parallel, we have performed linkage analysis in fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 18 publications
0
25
0
Order By: Relevance
“…Overall, the study found no excess in the number of LOD scores over 1, over that expected by chance, suggesting that all the peaks could be spurious. Other studies have suggested linkage to chromosomes 8p and 13q12-13 regions identified through loss of heterozygosity studies (Kerangueven et al, 1995;Seitz et al, 1997). Neither of these regions was, however, confirmed by either the BCLC study or the Finnish study.…”
Section: Progress In Finding Other Genesmentioning
confidence: 85%
“…Overall, the study found no excess in the number of LOD scores over 1, over that expected by chance, suggesting that all the peaks could be spurious. Other studies have suggested linkage to chromosomes 8p and 13q12-13 regions identified through loss of heterozygosity studies (Kerangueven et al, 1995;Seitz et al, 1997). Neither of these regions was, however, confirmed by either the BCLC study or the Finnish study.…”
Section: Progress In Finding Other Genesmentioning
confidence: 85%
“…Losses at 8p21-ter, detected by CGH, were not common in sporadic cancers in the studies of Iwabuchi et al (1995), Arnold et al (1996), and Sonoda et al (1997). There is mounting evidence from the literature that this region harbors an important tumor suppressor gene involved in a range of malignancies (Ishii et al, 1999), including laryngeal tumors (Rizos et al, 1998), prostate cancer (Watanabe et al, 1998), and sporadic female breast cancer Seitz et al, 1997;Wang et al, 1999), as well as male breast cancer (Tirkkonen et al, 1999). One candidate gene for this locus may be the Frizzled-related gene (Ugolini et al, 1999).…”
Section: Zweemer Et Almentioning
confidence: 94%
“…47 Furthermore, preliminary clinical data suggest, that tumors from Conserved A1 A2 B C D E 3 IVS2-7 Splice 4x 1 1 ? 3 353 A3G Y42C 38x 2 1 1 yes 3 451 G3C A75P 6x 1 1 yes 10 1199 G3C R324T 0x 1 1 yes 10 1206 C3A S326R 7x 1 1 no 10 1239 C3G N337K 0x 1 1 no 10 1379C3T S384F 12x 2 2 no 10 1570 C3T R448C 1x 1 1 no 10 1613 A3G E462G 9x 1 1 yes 11 2192 C3G P655R 23x 1 1 yes 11 2719 A3G V831I 0x 1 1 48 and for 13q21. 49 In summary, the BRCA1/BRCA2 mutation profile established for the German breast/ovarian cancer population facilitates the application of rapid prescreening strategies.…”
Section: Frequencies Of Brca Mutations In German Families and Searchmentioning
confidence: 99%